Carpentry, joinery and machine woodworking (Wood trades Part 1) - Emary, A.B. (London, United Kingdom : The Macmillan Press Limited, 1974)
This book has been written with the City and Guilds of London Institute Syllabuses for the Timber Trade (part 1) in mind, which are intended to cover the first year of the carpentry and joinery and machine woodworking crafts.
Preface -- 1. Materials -- 2. Tools -- 3. Joints -- 4. Portable powered hand tools -- 5.Woodcutting machinery -- 6. Ironmongery - 7. Turning pieces and centers for arches -- 8. Formwork for concrete -- 9. Ground floors -- 10. Roofs -- 11. Doors and frames -- 12. Single-light casement-windows -- 14. Technical drawing and geometry.
Keywords: JOINERY